Influence of autonomic nervous system in muscle activity of individual with sequelae after stroke. - Furmann, Meiriélly; Pires, Juliana Aparecida Wosch; Fréz, Andersom Ricardo; Kerppers, Ivo Ilvan; Salgado, Afonso Shiguemi Inoue; Shiraishi, Cristian Fernando; Ribeiro, Larissa Gulogurski; Rolão, Marcos Paulo Polowei; Suckow, Patricia Tyski (Manual Therapy, Posturology & Rehabilitation Journal, 2014)
Introduction: The stroke is a lesion of the Central Nervous System inducing spasticity, caused by a lesion of the upper motor neuron. The presence of spasticity limits the patient in achieving the necessary adjustments for the execution of required functional movements, causing limitations in daily life activities, interfering in our quality of life. Objective: To analyze the influence of the Autonomic Nervous System (ANS) in spastic patient consequential of stroke and decrease spasticity resulting of stimulus in the ANS. Method: It is a case study, where the spasticity was analyzed by means of Electromyography record (RMS), Ashowrth Scale modified and goniometry. The intervention consisted in 10 visits by performing Parasympathetic Laringe-Faringe Maneuvers, Plantar Arch and inhibition of Gastrocnemius. Results: The ANS has influence on the muscular activity, seen that there was a reduction of spasticity with decrease of the RMS values, increase in the amplitude of movement quantified by degrees and by means of the Modified Ashworth Scale. Conclusion: However, the mobilization of the autonomic nervous system through parasympathetic maneuvers are effective in decreasing spasticity due to stroke.